The Effectiveness of Media Literacy Training in Adolescent Internet Addiction - Abdollah Khaksar Azgandi; Majid Pakdaman; Hossain Kurashiki (پژوهان, 2023)
Background and Objectives: Media literacy training is one of the basic requirements; therefore, the aim of this study was to determine the effectiveness of media literacy training in adolescent Internet addiction. Materials and Methods: The quasi-experimental research method was pretest-posttest with a control group. From the statistical population that included all male students of the first year of high school in Torbat-e Heydarieh in the academic year 2021-2022, 30 people were selected by purposive sampling method and randomly divided into two groups of control and experimental. And answered the Young Internet Addiction Questionnaire (1999). The experimental group participated in 16 sessions of researcher-made media literacy training, but the group did not receive any training. SPSS software version 24 and univariate analysis of covariance were used for analysis. Results: The results of analysis of covariance showed that there was a significant difference between the scores of the experimental and control groups (pre-test and post-test) in the rate of Internet addiction (P < 0.01). Conclusions: The results showed that media literacy training reduced adolescent Internet addiction. Therefore, media literacy training is recommended as a complementary method along with psychological therapies to reduce adolescent Internet addiction.